Strike-slip Faulting during the 2014 Bárðarbunga-Holuhraun Dike Intrusion, Central Iceland. - Ágústsdóttir, Thorbjörg; Woods, Jennifer; Greenfield, Tim; Green, Robert G.; White, R. S.; Winder, Tom; Brandsdóttir, Bryndís; Steinthórsson, Sveinbjörn; Soosalu, Heidi (Geophysical Research Letters, 2016)
Over a 13 day period magma propagated laterally from the sub-glacial Bárðarbunga volcano in the northern rift zone, Iceland. It created > 30,000 earthquakes at 5–7 km depth along a 48 km path before erupting on 29 August 2014. The seismicity, which tracked the dike propagation, advanced in short bursts at 0.3–4.7 km/h separated by pauses of up to 81 hours. During each surge forward, seismicity behind the dike tip dropped. Moment tensor solutions from the leading edge show exclusively left-lateral strike-slip faulting sub-parallel to the advancing dike tip, releasing accumulated strain deficit in the brittle layer of the rift zone. Behind the leading edge, both left- and right-lateral strike-slip earthquakes are observed. The lack of non double-couple earthquakes implies that the dike opening was aseismic.